Academic, Political and Social Services of Mawlānā Sami’-ul-Ḥaq (Shahīd) - Muhammad Kamran,; Junaid Akbar,; Muhammad Ikramullah, (Journal of Islamic and Religious Studies, 2020)
Mawlānā Sami’-ul-Ḥaq (Shahīd) was a renowned Islamic Scholar, journalist, writer, politician, mujahid, and at the same time he was a wonderful leader and thinker on world affairs. In addition to teaching at the Dārul ‘Ulūm Ḥaqqāniyah Akora Khattak for almost sixty (60) years, he remained in active politics for forty-eight (48) years. He remained so close to the Afghans Jihād that in the Western world he was known as the "Father of the Taliban" and his madrassa as the "University of Jihad." Because of this fame, his academic, social, political, and community services were hidden from view. Due to his commitment to Afghan jihad and being the head of various religious and political movements, he has been the subject of debate in many circles. Questions have been raised about his academic credentials, commitment to the Afghan jihad, success rate in various religious and political movements, and the actual narrative of those movements. In addition to interviewing teachers at Dārul ‘Ulūm Ḥaqqāniyah and the people close to him, his personal writings, books, and articles about him have been used to find answers to all these questions. The study concludes that he was a reformer who played his role very well in different aspects of life.